Influence of phosphate anions on the stability of immobilized enzymes. Effect of enzyme nature, immobilization protocol and inactivation conditions - Kornecki, Jakub F.; Carballares, Diego; Sterlinga, Roberto Morellon; Siar, El Hocine; Kashefi, Saeid; Chafiaa, Mazri; Peña, Sara Arana; Rios, Nathalia Saraiva; Gonçalves, Luciana Rocha Barros; Lafuente, Roberto Fernandez (Process Biochemistry, 2021)
A destabilizing effect at pH 7 of sodium phosphate on several lipases immobilized via interfacial activation is shown in this work. This paper investigates if this destabilizing effect is extended to other inactivation conditions, immobilization protocols or even other immobilized enzymes (ficin, trypsin, β-galactosidase, β-glucosidase, laccase, glucose oxidase and catalase). As lipases, those from Candida antarctica (A and B), Candida rugosa and Rhizomucor miehei have been used. Results confirm the very negative effect of 100 mM sodium phosphate at pH 7.0 for the stability of all studied lipases immobilized on octyl agarose, while using glutaraldehyde-support the effect is smaller (still very significant using CALA) and in some cases the effect disappeared (e.g., using CALB). The change of the pH to 5.0 or 9.0, or the addition of 1 M NaCl reduced the negative effect of the phosphate in some instances (e.g., at pH 5.0, this negative effect is only relevant for CALB). Regarding the other enzymes, only the monomeric β-galactosidase from Aspergillus oryzae is strongly destabilized by the phosphate buffer. This way, the immobilization protocol and the inactivation conditions strongly modulate the negative effect of sodium phosphate on the stability of immobilized lipases, and this effect is not extended to other enzymes 2030-12